Pengaturan Alat Peraga Kampanye Dalam Pelaksanaan Pemilihan Kepala Daerah - Choirul Anam (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2018)
This study aims to explain the mechanism for electing governors and deputy governors, regents and deputy regents as well as mayors and deputy mayors who are directly elected by the people, through what we are familiar with direct regional head elections and to find out the authority of the general election commission (KPU ) in conducting the procure- ment, distribution and installation of campaign props (APK.) The method used in this research is legal research which is to find the rule of law, legal principles, and legal doc- trines in order to answer the legal issues encountered. In this study shows that given the authority of political parties or candidate pairs to hold campaign props a number of prob- lems arise, including the difficulty for the KPU to control or control campaign props held by political parties or candidate pairs starting from the number, completion time, until the design